2022
DOI: 10.1186/s12902-022-01111-6
|View full text |Cite
|
Sign up to set email alerts
|

Body fat assessment in youth with overweight or obesity by an automated bioelectrical impedance analysis device, in comparison with the dual-energy x-ray absorptiometry: a cross sectional study

Abstract: Background Bioelectrical impedance analysis (BIA) is a widely used method to assess total body fat (TBF) depots characterising obesity. Automated BIA devices provide an inexpensive and easy assessment of TBF, making them widely available to the general public and healthcare providers without specific qualification to assess body composition. The equations included in the automated BIA devices have been developed in very few specific populations, which means that they are not suitable to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…6,7 Similar to this study's findings, other research has concluded that BIA devices differ significantly in their BC accuracy compared to gold standards such as DEXA. 4,5 Methodological Considerations:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Similar to this study's findings, other research has concluded that BIA devices differ significantly in their BC accuracy compared to gold standards such as DEXA. 4,5 Methodological Considerations:…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that BIA devices differ significantly in their BC accuracy compared to gold standard methods such as dual-energy x-ray absorptiometry (DEXA). 4,5 Other research has produced more positive results for the efficacy of BIA devices. Two studies found BIA to be a valid and accurate method for measuring BC equivalent to gold standard methods such as DEXA and magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%
“…Weight and height measurements, offer a simpler and quicker alternative, with Body Mass Index (BMI) being a widely employed metric (3). BMI's limitations include its inability to differentiate between muscle, fat, bone, or vital organs, leading to misclassi cation of individuals with high fat-free mass (FFM) relative to stature as overweight or obese, and its failure to account for variations in body composition among individuals (4,5). Moreover, body fat percentage (BF%) varies with age, sex, ethnicity, and individual differences, complicating the interpretation of BMI values (6).…”
Section: Introductionmentioning
confidence: 99%
“…BIA devices incorporate predictive equations for body fat that were originally developed using data from speci c demographic groups (4,12). Many of these equations were initially derived from studies involving predominantly white populations and subsequently applied to individuals from diverse ethnic backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, even dual-frequency BIA can show large differences from DXA 31 . In studies of obese and diseased children, single-frequency BIA has shown discrepancies with DXA 32 , 33 . Impedance is a function of reactance and resistance 28 , 34 , and a potential solution to this problem is to incorporate technology that can measure reactance, making it possible for even a single-frequency BIA device to acquire information that reflects not only the resistance of the extracellular fluid, but also information from the cell membrane, thereby improving the accuracy of the measurements.…”
Section: Introductionmentioning
confidence: 99%